Effect of Lactobacillus casei on the Pharmacokinetics of Amiodarone in Male Wistar Rats - Matuskova, Zuzana; Anzenbacher, Pavel; Vecera, Rostislav; Siller, Michal; Tlaskalova-Hogenova, Helena; Strojil, Jan; Anzenbacherová, Eva (European journal of drug metabolism and pharmacokinetics, 2017)
BACKGROUND AND OBJECTIVES: The probiotic bacterium Escherichia coli strain Nissle 1917 has previously been shown to alter the pharmacokinetics of amiodarone. The aim of this study was to determine whether the probiotic bacterium Lactobacillus casei produces similar alterations in amiodarone disposition. METHODS: A suspension of live probiotic bacteria L. casei strain DN-114 001 (1.5 × 10(9) CFU/dose; probiotic pre-treated group) or a saline solution (control group) was administered directly into the stomach of male Wistar rats (N = 30 in each group) by oral gavage daily for 7 consecutive days. On the eighth day, all rats (N = 60) were given a single oral dose of an amiodarone hydrochloride suspension (model drug; 50 mg/kg). The concentrations of amiodarone and of its main metabolite N-desethylamiodarone were determined in rat plasma by high-performance liquid chromatography. RESULTS: Comparison of the pharmacokinetics of amiodarone in the control group and probiotic pre-treated group revealed that the peak plasma concentration of amiodarone was delayed by >2 h in the probiotic pre-treated group. The plasma level of N-desethylamiodarone was unchanged in the probiotic pre-medicated group and its pharmacokinetic parameters were not altered. CONCLUSIONS: The slower absorption of amiodarone in the probiotic pre-treated rats compared to the control ones and the unchanged pharmacokinetics of its main metabolite suggest that the probiotic strain of L. casei DN-114 001 has probably no clinical consequences as the difference was not statistically significant.
Keywords: amiodaron; Probiotics; Male; Administration, Oral; Rats; mužské pohlaví; Lacticaseibacillus casei; zvířata; krysa rodu Rattus; Animals; Amiodarone; aplikace orální; probiotika; Lactobacillus casei